Respuesta :

Answer:

B) − 2/9

Explanation:

[tex]\hookrightarrow \sf \dfrac{11}{18} * -\dfrac{4}{11}[/tex]

join both fractions

[tex]\hookrightarrow \sf \dfrac{11*-4}{18*11}[/tex]

simplify by multiplying

[tex]\hookrightarrow \sf \dfrac{-44}{198}[/tex]

simplify the following

[tex]\hookrightarrow \sf -\dfrac{2}{9}[/tex]

[tex]\bold{Heya!}[/tex]

Answer :-

B) [tex]\sf{-\frac{2}{9}[/tex]

→  EXPLANATION :

[tex]\sf{\frac{11}{18}(-\frac{4}{11})[/tex]

Apply rule :  [tex]\sf{a(-b) = -ab}[/tex]

[tex]\sf{\frac{11}{18}(-\frac{4}{11}) = -\frac{11}{18}[/tex] × [tex]\sf{\frac{4}{11}[/tex]

[tex]\sf{= -\frac{11}{18}[/tex] × [tex]\sf{\frac{4}{11}[/tex]

Cross - cancel common factor: [tex]\sf{11}[/tex]

[tex]\sf{= -\frac{4}{18}[/tex]

Factor the number: [tex]\sf{4 = 2}[/tex] × [tex]\sf{2}[/tex]

[tex]\sf{= -\frac{2 \: x \: 2}{18}[/tex]

Factor the number: [tex]\sf{ 18 = 2 \: x \: 9}[/tex]

[tex]\sf{= - \frac{2 \: x \: 2}{2 \: x \: 9}[/tex]

Cancel common factor: [tex]\sf{2}[/tex]

[tex]\sf{-\frac{2}{9}[/tex]

Hopefully This Helps ! ~

#LearnWithBrainly

[tex]\underline{Answer :}[/tex]

Jaceysan ~